PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI FUNGSI KOMPOSISI DI KELAS X SMAN 5 PALU: Application of Problem Based Learning (PBL) Model to Improve Students' Learning Outcomes on Composition Function Material in Class X of SMAN 5 Palu - Irawati Irawati; Anggraini Anggraini; Baharuddin Paloloang (Universitas Tadulako, 2025)
This research aims to obtain a description of the implementation of problem based learning model to improve student learning outcomes in grade X MIPA 3 SMA Negeri 5 Palu on composition of function. This type of research was Classroom Action Research. The research design refers to the model of Kemmis and Mc. Taggart. This research was located at SMA Negeri 5 Palu. The subjects of this study were 30 students of grade X MIPA 3. The results of the research show that the implementation of problem-based learning modelcan improve student learning outcomes, with the following stages: 1) basic concepts;. 2) defining the problem; 3) self-study; 4) study groups; 5) assessment; The increase of students learning outcomes based on the results final test: Action in cycle I is 73.33% and cycle II is 83.33%. The result of observation of teacher activity in cycle I is in the category of sufficient. In cycle II, the total score on the result of the observation of teacher and student activity in cycle II is in good category. The resultindicates that the implementation of Problem Based Learning (PBL) model can improve students learning outcomes on composition of function in grade X of MIPA 3 SMA Negeri 5 Palu.